The Impact of Industrial Air Pollution on the Urban Environment of Setif: Modeling and Mapping of Total Suspended Particles - Harkat, N.; Rahmane, A.; Bendjemila, I. (Engineering, Technology & Applied Science Research, 2022)
Setif is one of the urban agglomerations most exposed to the problem of air pollution, which mostly arises from the industrial zone located on its immediate outskirts, as is the case with a large number of Algerian cities. Due to its size and the nature of its activities, Setif is a significant source of industrial pollution. Numerous experts agree that the majority of present air pollution analysis techniques are limited to predicting the dispersion of pollutants. However, restricting oneself to these usually rigid aspects impedes the proper management of this sort of urban nuisance harming the city and its surroundings. Consequently, the aim of this study is to propose an approach for assessing the danger of air pollution that can be simply applied to any terrain. This technique includes three primary stages. Initially, ARIA Impact software is used to develop a model of the Total Suspended Particles (TSP). Using the Analytic Hierarchy Process technique, the many human, material, and environmental issues are then plotted on a map. The last step is to build synthesis maps by crossing the theme maps developed in the first two steps. Consequently, the anticipated outcome of this study is that the industrial zone of Setif will serve as the basis for a methodological exercise generated from a real-world situation. The examination of the current case study will illustrate the reliability of dispersion models in the evaluation of industrial pollution provided that certain essential aspects are recognized and handled effectively.